2015
DOI: 10.1038/ncomms6968
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical instability at finite temperature

Abstract: Many physical systems including lattices near structural phase transitions, glasses, jammed solids and biopolymer gels have coordination numbers placing them at the edge of mechanical instability. Their properties are determined by an interplay between soft mechanical modes and thermal fluctuations. Here we report our investigation of the mechanical instability in a lattice model at finite temperature T. The model we used is a square lattice with a f 4 potential between next-nearest-neighbour sites, whose quad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 54 publications
4
52
0
Order By: Relevance
“…38 If the structural ground state of black phosphorene (BP), black arsenene, and monochalco- Figure 1: (a) The elastic energy landscape E(a 1 , a 2 ) as a function of lattice parameters a 1 and a 2 is generic to all monolayers with a Pnma structure, and it is exemplified on a GeS monolayer at zero temperature. A dashed white curve joins points A and B at two degenerate minima (E A = E B = 0).…”
Section: Introductionmentioning
confidence: 99%
“…38 If the structural ground state of black phosphorene (BP), black arsenene, and monochalco- Figure 1: (a) The elastic energy landscape E(a 1 , a 2 ) as a function of lattice parameters a 1 and a 2 is generic to all monolayers with a Pnma structure, and it is exemplified on a GeS monolayer at zero temperature. A dashed white curve joins points A and B at two degenerate minima (E A = E B = 0).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that, while sublinear scaling is not confined to lattice models, the exponent does depend on the topology of the network. Indeed, in a recent paper [30] it was found that a square-lattice network with nextnearest-neighbor interactions, which is at the isostatic point when the next-nearest-neighbor interactions are zero, showed a critical regime where G ∝ T α with α ∼ 0.66, different from the α ∼ 0.5 observed both in Ref. [29] for a diluted-triangularlattice network at the isostatic point and in the random-bond networks presented here (see Fig.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…Indeed, in Ref. [30] a square lattice (which is at the isostatic point) with next-nearestneighbor interactions was found to stiffen with a different critical exponent than a randomly diluted triangular lattice also at the isostatic point [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the topologically nontrivial phase all floppy modes localize on the top edge leaving the bottom edge rigid. This physics of the Maxwell lattices make them both an interesting topic for theoretical study [21][22][23][24][25][26][27] and good candidates for the design of novel mechanical metamaterials where the edges can change stiffness by orders of magnitude reversibly [17].…”
mentioning
confidence: 99%